The context of postnatal depression in Malaysia: an overview - Mohd Arifin, Siti Roshaidai; Cheyne, Helen; Maxwell, Margaret (2018)
Sociocultural contexts of motherhood have been found to have a link with postnatal depression. Malaysia has a wide-range of cultural and ethnic backgrounds that offers a wonderful chance to understand the different role of cultures and postnatal practices in relation to postnatal depression. The purpose of this paper is to discuss the link between the Malaysian healthcare system, social and cultural context, the existing health policy and postnatal depression. This paper highlights that while there are different levels of nurses who work collaboratively to manage pregnant and postnatal mothers in the maternal and child health clinic, the focus of their care is more on physical health. The international guidelines for diagnosing PND were not commonly used within the clinics, although the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) has been widely used within psychiatric setting in Malaysia. There is no formal mechanism or assessment to detect PND in the clinics. There were no guidelines found that specifically focused on the management of PND. It is questionable whether the current approaches to promote and manage maternal mental health in Malaysia have a sense of cultural-based strategies. These significant gaps call for empirical evidence that explicitly focussed on the experiences and perceptions of PND in Malaysia.